2017
DOI: 10.3389/fimmu.2017.01538
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Secretory Leukoprotease Inhibitor As an Endogenous Negative Regulator in Allergic Effector Cells

Abstract: Mast cells, basophils, and eosinophils are central effectors in allergic inflammatory disorders. These cells secrete abundant serine proteases as well as chemical mediators and cytokines; however, the expression profiles and functions of their endogenous inhibitors remain elusive. We found that murine secretory leukoprotease inhibitor (SLPI) is expressed in basophils and eosinophils but in not in mast cells. SLPI-deficient (Slpi−/−) basophils produce more cytokines than wild-type mice after IgE stimulation. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Elevated levels of both eosinophils and SLPI in tissues affected by allergy-associated inflammatory diseases suggest that eosinophils may be a source and/or target of SLPI. This is in line with a recent study that demonstrated that SLPI is expressed in mouse eosinophils and that the ability of SLPI-deficient murine eosinophils to secrete IL-6 and express metalloproteinase-9 (MMP-9) is diminished ( 13 ). However, SLPI expression and/or function in human eosinophils remain unknown.…”
Section: Introductionsupporting
confidence: 90%
“…Elevated levels of both eosinophils and SLPI in tissues affected by allergy-associated inflammatory diseases suggest that eosinophils may be a source and/or target of SLPI. This is in line with a recent study that demonstrated that SLPI is expressed in mouse eosinophils and that the ability of SLPI-deficient murine eosinophils to secrete IL-6 and express metalloproteinase-9 (MMP-9) is diminished ( 13 ). However, SLPI expression and/or function in human eosinophils remain unknown.…”
Section: Introductionsupporting
confidence: 90%
“…SLPI is known to have the ability to directly penetrate cells to inhibit nuclear factor κB (NF-κB) signaling ( Taggart et al, 2005 ), and exogenously administered SLPI ( Wright et al, 1999 ), as well as SLPI expressed from a transgene ( Marino et al, 2011 ; Raundhal et al, 2015 ), reduces eosinophilic inflammation in models of AAI. Additionally, SLPI has been demonstrated to be an endogenous regulator of eosinophil and basophil function by inhibiting Toll-like receptor 4 (TLR4) signaling in allergic inflammation ( Matsuba et al, 2017 ). However, more studies investigating the tissue-specific effects of SLPI resulting from airway bacterial colonization will be needed to address which cell types and molecular targets are affected by SLPI and mediate protection from AAI.…”
Section: Discussionmentioning
confidence: 99%
“…These anti-inflammatory mechanisms likely form the basis of positive outcomes observed for treatment with SLPI in animal models for inflammatory diseases such as arthritis ( 11 , 12 ) and healing of chronic wounds ( 6 , 13 ). In addition, genetic deletion of SLPI in eosinophils and basophils results in increased allergic inflammation ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently discovered the slpi gene to be one of the only three genes significantly altered in MMP-9 KO mice compared to WT mice ( 32 ). In addition, others found that SLPI-deficient eosinophils have increased MMP-9 gene transcription ( 14 ). These and other studies point toward reciprocal regulation of SLPI and MMP-9 and impose to further investigate a possible link between MMP-9 and SLPI.…”
Section: Introductionmentioning
confidence: 99%